LATVIAN CONCEPT MUSIC: HISTORICAL AND THEORETICAL ISSUES (Mūzikas akadēmijas raksti, 2024)
The article encompasses research results during doctoral studies in musicology, and characterizes the most recent music of Mārtiņš Viļums, Jānis Petraškevičs, Santa Ratniece, Ruta Paidere and other composers. The term ‘concept’ in different forms has been used in the Latvian musicology for over a decade already, but has not been strictly defined until now.